2018
DOI: 10.1007/s11238-018-9665-9
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of third parties’ preference for compensation over punishment: six experimental demonstrations

Abstract: Research suggests that to restore equity, third parties prefer compensation of a victim over the punishment of a perpetrator. It remains unclear, however, whether this preference for compensation is stable or specific to certain situations. In six experimental studies, we find that adjustments in the characteristics of the situation or in the available behavioral options hardly modify the preference of compensation over punishment. This preference for compensation was found even in cases where punishment might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…This assertion is supported by Gummerum et al () who found that participants were more willing to compensate the victim when manipulated to experience the victims' feelings from the victim’s perspective. Van Doorn and Brouwers () posit that participants choose to compensate the victim for various reasons such as in order to gain the victims respect or because they care about the victim as an ingroup member. Further support for this argument comes from neuroimaging studies that demonstrate individuals hold attentional bias towards ingroup members when perceiving injustice (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This assertion is supported by Gummerum et al () who found that participants were more willing to compensate the victim when manipulated to experience the victims' feelings from the victim’s perspective. Van Doorn and Brouwers () posit that participants choose to compensate the victim for various reasons such as in order to gain the victims respect or because they care about the victim as an ingroup member. Further support for this argument comes from neuroimaging studies that demonstrate individuals hold attentional bias towards ingroup members when perceiving injustice (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Still, such helping need not be limited to close ones. Van Doorn et al (2018aDoorn et al ( , 2018b and Van de Vyver and Abrams (2015), as discussed previously, have shown that people also preferred compensation to punishment in cases of unacquainted victims of injustice.…”
Section: (Social) Benefitsmentioning
confidence: 79%
“…Previous findings indicate that people were willing to spend more game money on compensation than punishment (e.g. Chavez & Bicchieri, 2013;Lotz et al, 2011;Van de Vyver & Abrams, 2015;Van Doorn et al, 2018a, 2018b. However, in more real-life scenarios (tax dodging or robbery), as used in studies by Van de Vyver and Abrams (2015) and Van Prooijen (2010), this preference was not found.…”
Section: Crime Severitymentioning
confidence: 93%
See 2 more Smart Citations